Neurotransmitters behind pain relief with transcranial magnetic stimulation - positron emission tomography evidence for release of endogenous opioids - Lamusuo, S; Hirvonen, J; Lindholm, P; Martikainen, I K; Hagelberg, N; Parkkola, R; Taiminen, T; Hietala, J; Helin, S; Virtanen, A; Pertovaara, A; Jääskeläinen, S K (European journal of pain, 2017)
Repetitive transcranial magnetic stimulation (rTMS) at M1/S1 cortex has been shown to alleviate neuropathic pain. To investigate the possible neurobiological correlates of cortical neurostimulation for the pain relief. We studied the effects of M1/S1 rTMS on nociception, brain dopamine D2 and μ-opioid receptors using a randomized, sham-controlled, double-blinded crossover study design and 3D-positron emission tomography (PET). Ten healthy subjects underwent active and sham rTMS treatments to the right M1/S1 cortex with E-field navigated device. Dopamine D2 and μ-receptor availabilities were assessed with PET radiotracers [ C]raclopride and [ C]carfentanil after each rTMS treatment. Thermal quantitative sensory testing (QST), contact heat evoked potential (CHEP) and blink reflex (BR) recordings were performed between the PET scans. μ-Opioid receptor availability was lower after active than sham rTMS (P ≤ 0.0001) suggested release of endogenous opioids in the right ventral striatum, medial orbitofrontal, prefrontal and anterior cingulate cortices, and left insula, superior temporal gyrus, dorsolateral prefrontal cortex and precentral gyrus. There were no differences in striatal dopamine D2 receptor availability between active and sham rTMS, consistent with lack of long-lasting measurable dopamine release. Active rTMS potentiated the dopamine-regulated habituation of the BR compared to sham (P = 0.02). Thermal QST and CHEP remained unchanged after active rTMS. rTMS given to M1/S1 activates the endogenous opioid system in a wide brain network associated with processing of pain and other salient stimuli. Direct enhancement of top-down opioid-mediated inhibition may partly explain the clinical analgesic effects of rTMS. Neurobiological correlates of rTMS for the pain relief are unclear. rTMS on M1/S1 with C-carfentanyl-PET activates endogenous opioids. Thermal and heat pain thresholds remain unchanged. rTMS induces top-down opioid-mediated inhibition but not change the sensory discrimination of painful stimuli.